Cross-reactive IgE antibody responses to tropomyosins from Ascaris lumbricoides and cockroach - Santos, Ana Beatriz R.; Rocha, Gutemberg M.; Oliver, Constance; Ferriani, Virginia P. L.; Lima, Rodrigo C.; Palma, Mario Sergio [UNESP]; Sales, Valdria S. F.; Aalberse, Rob C.; Chapman, Martin D.; Arruda, L. Karla (Mosby-elsevier, 2008)
Background: Evidence indicates that infection with Ascaris lumbricoides may promote development of allergy and asthma.Objective: To study the role of tropomyosin, a pan-allergen in invertebrates, in IgE responses to A lumbricoides.Methods: Recombinant A lumbricoides and Periplaneta americana tropomyosins were expressed in Pichia pastoris. Levels of IgE to tropomyosins from A lumbricoides and P americana were determined by chimeric ELISA in sera from 119 children living in a parasite-endemic area and 112 patients with cockroach allergy from the allergy clinics. Presence of tropomyosin in A lumbricoides larvae at L3 stage was evaluated by immunofluorescence using mAb IA6, directed against mite tropomyosin. Molecular modeling of P americana and A lumbricoides tropomyosins was performed by using the MODELLER program.Results: A lumbricoides tropomyosin showed 69% to 98% sequence identity to tropomyosins from other invertebrates. The predicted structure of A lumbricoides tropomyosin was similar to that of P americana tropomyosin and showed the characteristic coiled-coil structure. Strong correlation was found for IgE antibodies to tropomyosins from A lumbricoides and P americana in sera from children living in a parasite-endemic area and from patients with cockroach allergy. Larvae of A lumbricoides reacted strongly with mAb IA6.Conclusion: Tropomyosin induces IgE responses in A lumbricoides-infected children and in patients allergic to cockroach.
Keywords: tropomyosin; Ascaris lumbricoides; periplaneta americana; IgE cross-reactivity; allergy; parasites; asthma